2022
DOI: 10.1186/s12959-021-00358-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between obstructive sleep apnea and venous thromboembolism recurrence: results from a French cohort

Abstract: Background Growing evidence suggests the relationship between obstructive sleep apnea (OSA) and venous thromboembolism (VTE). Few studies focused on VTE recurrence risk associated with OSA after anticoagulation cessation. Methods In a prospective cohort study, patients with documented VTE, were followed for an indefinite length of time and VTE recurrence were documented and adjudicated. The primary outcome was recurrent VTE after anticoagulation di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Excess adipose tissue in individuals with obesity can lead to chronic inflammation and an imbalance in the production of prothrombotic factors, thereby increasing the risk of both OSA and VTE. The visceral fat accumulation further exacerbates these effects, creating a vicious cycle of inflammation and thrombogenesis [ 2 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Excess adipose tissue in individuals with obesity can lead to chronic inflammation and an imbalance in the production of prothrombotic factors, thereby increasing the risk of both OSA and VTE. The visceral fat accumulation further exacerbates these effects, creating a vicious cycle of inflammation and thrombogenesis [ 2 ].…”
Section: Reviewmentioning
confidence: 99%
“…Given the emerging association between OSA and VTE, it is crucial to prioritize the screening and identification of OSA in patients with VTE. Healthcare providers should be vigilant and recognize the potential coexistence of these conditions, understanding that addressing OSA in VTE patients may have significant clinical implications [ 2 ]. When evaluating patients with VTE, healthcare providers should consider the possibility of underlying OSA, particularly in individuals who share common risk factors such as obesity, older age, and comorbidities.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of observational studies remain somewhat controversial. A five-year prospective study involving 2109 subjects concluded that OSA did not increase the risk of VTE recurrence [13]. Another retrospective analysis involving 1,584 patients, of which 848 were women, revealed an intriguing discovery suggesting that OSA may serve as an independent risk factor for VTE solely in women, rather than in men [14].…”
Section: Introductionmentioning
confidence: 99%
“…A 5-year prospective study involving 2,109 subjects concluded that OSA did not increase the risk of VTE recurrence. 13 Another retrospective analysis involving 1,584 patients, of which 848 were women, revealed an intriguing discovery suggesting that OSA may serve as an independent risk factor for VTE solely in women, rather than in men. 14 Moreover, patients with VTE were found to have a higher prevalence of OSA, 15 suggesting a potential bidirectional relationship.…”
Section: Introductionmentioning
confidence: 99%